Strategic Role Of The Legal Bureau Of The Regional Secretariat Of Central Kalimantan Province In Harmonizing Draft Regional Regulations - Debagus, Debagus; Al-Riski, M.Akhmal; Sagita, Fitria Auliani; Sulistyawati, Dessy; Agustin, Imel; Hasuna, Kamal (Fakultas Hukum Dehasen, 2025)
In the context of the implementation of regional autonomy, the Legal Bureau of the Central Kalimantan Provincial Secretariat plays a strategic role in harmonizing the draft regional regulations (RPD). Through qualitative research, it is explained how the Legal Bureau carries out its responsibilities in harmonizing, adjusting, consolidating, and rounding the concept of RPDA with higher, equivalent, or lower laws and regulations. This Legal Bureau is a vertical agency that is active in harmonizing RPDs, ensuring that RPDs are prepared systematically without conflicting or overlapping with each other. The results of the study show that the role of the Legal Bureau is very effective in monitoring the RPD harmonization process in accordance with its elements, such as the order of authority, orderly procedures, and relevant substances.